Pengembangan Video Pembelajaran dengan Bantuan Software Wondershare Filmora pada Materi Reaksi Reduksi Oksidasi - Lolita A M Parera; Heru Christianto; Antonius Petrus Pana Lazar (Universitas Negeri Medan, 2022)
This research aims to determine the form of the development of learning videos on the subject matter of oxidation reduction reactions (redox) with the help of wondershare filmora software so that they can become effective media in the learning process and to determine their feasibility. The procedure taken to produce the product is divided into 4 stages, namely: (1) determining the material to be developed, (2) carrying out design and development, (3) producing wondershare filmora software or packaging learning videos, and (4) conducting a formative evaluation and revise development product. The results of the assessment from material experts and media experts on the feasibility of this learning video have a very good category with an overall ideal percentage of 84,69% each in terms of the material presented and 90.5% in terms of the media displayed. The results of the peer reviewer test assessment of this learning video is 80,9% with a very good category. As for the results of the assessment of student responses to this learning, it is included in the very good category with an ideal percentage of 97.25% for small group trials and 98.75% for large group trials, respectively. Keywords: Development, Learning Video, Wondershare Filmora, Oxidation Reduction Reaction